Relationship Between the Personality Type and Work Life Balance Among Academic Staff of University of Kelaniya - Padmasiri, M.K.D.; Mahalaekamge, W.G.S. (Department of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka, 2013)
The focus of this research is to find out the impact of different types of personality and Work Life Balance (WLB) of academic staff of University of Kelaniya. Researchers used standardized personality assessment named as Myers-Briggs Type Indicator (MBTI) to assess the type of personality. Objectives are, to examine the impact of personality type of academic staff in University of Kelaniya on their WLB, to identify the level and type of personality of academic staff, to identify the level of WLB of academic staff and to recommend suitable personality type for WLB. Research sample consisted with 180 lecturers out of 560 University of Kelaniya. Standardized questionnaire used to collect data. Collected data analyzed and evaluated manually as well as using the SPSS and Excel. By considering the nature of the study conducted an Anova test. According to MBTI there are 16 personality types where one personality consists with 4 indicators. Indicators are as follow, IIntroversion, E-Extraversion, S- Sensing, I- Intuition, T- Thinking, FFeeling, J- Judging, P- Perception. In sample ISFJ, ISTJ, ESFJ and ENFJ each personality type have 4 indicators, ISFP, INTP, ESTJ and ENTJ each personality type has 3 indicators, INFJ has 2 indicators and INTJ, ISTP, ESTP, ENFP and ENTP each personality has only 1 indicator. According to the findings ISTP, ISFP, INTP, ESTP, ESFP, ISTJ, ENFP, ENTP, ESTJ, ESFJ, ENFJ, ENTJ personality have work life balance but people who have ISFJ, INFJ, INTJ, INFP personality have moderately balanced work life. There are no WL imbalance respondents. Sample consisted with 133 females & 47 males. Mean value of females and males are 36.57 and 34.44. Researcher recommended to enhance Extraversion, Intuition and Feeling indicators to execute the responders’ teacher career effectively. And suggested to enhance ENTP which emphasized Visionary career and its well match with the teacher career. Finally recommended to INTJ personality responders to attempt to change N indicator to become S by enhancing sensing abilities to balance WL. Further research areas are find WLB of academic staff with each personality type but respond to gender differentiation, marital status differences.
Keywords: MBTI; Personality; Work life balance